Análise das barreiras e incentivos para a implantação da energia fotovoltaica na Paraíba - Cavalcante, Rafael de Carvalho (2018)
With technological development and its repercussions in all spheres of modern life, electric energy assumes the role of essential good for life in society, having an influence on both economic and public health issues. Given this essentiality, a special question arises as to its production mode and how it can affect the quality of life of future generations. It is known that non-renewable energy sources have an immense potential for damaging the environment, but only when the results of decades of degradation become palpable does the interest arise in seeking alternative means of production that are committed to sustainable development. In this context of environmental awareness in energy production, not long ago, European and Asian countries pioneered in the production of photovoltaic energy, a type of renewable energy. Although Brazil possesses several characteristics to occupy a relevant place in the production of such type of energy, because it has particularly favorable weather and irradiation conditions, it falls far short of the use of its potential in terms of energy use. Therefore, this study seeks to analyze the barriers that impede the development of photovoltaic energy, especially in the Brazilian state of Paraíba, by using a bibliographic and documentary research based on periodicals, books and databases to compare incentive programs that have influenced the development of photovoltaic energy in countries such as China, Germany and Japan (Feed-inTariff, tax reductions and tax credits). In addition, questionnaires were used to verify, in the opinion of a group of stakeholders, which factors interfere most in the local scenario. The results obtained guarantee the importance of government participation in the growth and development of photovoltaic energy in Brazil. Without efficient regulatory action, whether through political or economic incentives, this will hardly happen or will take much longer to occur than it really should.